Screening the Prevalence of Rubella Virus Infection Using Enzyme Linked Immunosorbent Assay (ELISA) and Electrochemiluminescence (ECL) Diagnostic Techniques among Pregnant Women in Mukalla City, Hadhramout/Yemen - Eidha Ali Bin-Hameed (Enhanced Knowledge in Sciences and Technology, 2022)
Background: Infection with Rubella virus is a public health concern because it may lead to serious consequences such as congenital rubella syndrome (CRS) during early pregnancy. The sero-prevalence rates of the Rubella virus among pregnant women vary widely throughout the world. Objective: This study was aimed to determine the prevalence of Rubella virus infection and associated risk factors among pregnant women in Mukalla city, Hadhramout/Yemen. Materials and methods: In this cross-sectional and hospital-based study, the serum samples were collected from 190 pregnant women, then screened for Rubella virus antibodies (IgG and IgM) using enzyme linked immunosorbent assay (ELISA) and electrochemiluminescence (ECL) immunoassay techniques. Qualitative data regarding risk factors for rubella infection were assessed in participants interview using a questionnaire including socio-demographic and reproductive variables. Findings: The results indicated that among the tested pregnant women, there was a high seropositive cases of anti-rubella IgG 136(71.6%), while the seropositive cases of anti-rubella IgM was 17(8.9%). The proportion of pregnant women who were rubella IgG positive was significantly dependent on the age groups 15–30 years of the pregnant women (COR=0.749, 95%CI=0.113-0.557, P=0.001) and the moderate level income (COR=0.761, 95%CI=0.075-0.760, P=0.015). Anti-IgM positive rubella infection had a significant relationship with the pregnant women miscarriage (COR=0.925, 95%CI=0.020-.283, P=0.00), and the risk of contracting Rubella virus infection was found to increase with history of live births with a statistical significance (COR=1.942, 95%CI=1.020-3.695, P=0.043). ELISA technique proved to be high sensitivity, specificity and accuracy for detecting Rubella virus infection. Conclusion: the prevalence rate of rubella infection was relatively high in Mukalla city, Hadhramout and are significantly associated with an increase in age and income level, and the risk of contracting rubella infection was found to increase with gestational age and associated with miscarriage. Screening of rubella and immunization of women are highly recommended in this setting.